Application of electrospun nanofibers in bone, cartilage and osteochondral tissue engineering. Issue 4 (16th November 2020) - Ding, Huixiu; Cheng, Yizhu; Niu, Xiaolian; Hu, Yinchun
Abstract: Tissue damage related to bone and cartilage is a common clinical disease. Cartilage tissue has no blood vessels and nerves. The limited cell migration ability results in low endogenous healing ability. Due to the complexity of the osteochondral interface, the clinical treatment of osteochondral injury is limited. Tissue engineering provides new ideas for solving this problem. The ideal tissue engineering scaffold must have appropriate porosity, biodegradability and specific functions related to tissue regeneration, especially bioactive polymer nanofiber composite materials with controllable biodegradation rate and appropriate mechanical properties have been getting more and more research. The nanofibers produced by electrospinning have high specific surface area and suitable mechanical properties, which can effectively simulate the natural extracellular matrix (ECM) of bone or cartilage tissue. The composition of materials can affect mechanical properties, plasticity, biocompatibility and degradability of the scaffold, thereby further affect the repair efficiency. This article reviews the characteristics of polymer materials and the application of its electrospun nanofibers in bone, cartilage and osteochondral tissue engineering.